The Frequency of Langerhans Islets β-Cells Autoantibodies (Anti-GAD) in Georgian Children and Adolescents with Chronic Autoimmune Thyroiditis - Mariam Balakhadze; Elene Giorgadze; Marina Lomidze (International Journal of Endocrinology)
Aim. Chronic autoimmune thyroiditis and type 1 diabetes mellitus are organ-specific autoimmune diseases. There is large evidence that autoimmunity against the thyroid gland in patients with type 1 diabetes mellitus is increased, but little is known about anti-islet cell autoimmune status in patients with chronic autoimmune thyroiditis. We evaluated the concentration of antibodies against glutamic acid decarboxylase (GAD) which are widely used as a diagnostic and predictive tool for type 1 diabetes mellitus, in school-aged Georgian children with chronic autoimmune thyroiditis. Methods. The frequency of anti-GAD antibodies was measured in Georgian school-aged children with chronic autoimmune thyroiditis and compared to healthy age and sex matched controls. Results. Of the 41 patients with chronic autoimmune thyroiditis 4 (9.8%) were positive for GAD antibodies. The frequency of GAD positivity in the chronic autoimmune thyroiditis group was significantly higher than in the control subjects (P=0.036). Conclusion. In the study we found that the frequency of GAD antibody positivity in autoimmune thyroiditis patients was significantly higher (9.8%, P=0.036) than in the control group. Our findings support the concept that patients with autoimmune thyroid disease may develop type 1 diabetes mellitus in future life.